Growth, wood density and bark thickness of silver birch originating from the Baltic countries and Finland in two Finnish provenance trials - Viiherä-Aarnio, Anneli; Velling, Pirkko (The Finnish Society of Forest Science, 2017)
Silver birch (Betula pendula Roth) seed origins from the Baltic countries and from Finland were compared in terms of growth, wood density, bark thickness and the incidence of darkened core wood, frost cracks and decay, and the effect of seed origin latitude was examined in two Finnish provenance trials. The material consisted of 21 stand and single tree origins ranging from latitudes 54° to 63°N from the Baltic countries and Finland. The trials, measured at the age of 22 years, were located at Tuusula (60°21´N), southern Finland and at Viitasaari (63°11´N), central Finland. The Baltic origins were superior to the Finnish ones in the southern trial regarding height, whereas in central Finland the Finnish origins grew better. There was no consistent difference between the Baltic and the Finnish group of origins in wood density. Bark thickness decreased with increasing seed origin latitude. The Baltic origins had significantly thicker bark than the Finnish origins. A moderate positive correlation was detected between the seed origin latitude and the incidence of darkened core wood in the southern trial, where the darkened core wood was more common in the Finnish origins than in the Baltic ones. The highest proportion of trees with frost cracks was detected in the south-western Latvian origins growing in central Finland. Seed transfers from the Baltic would have an increasing effect on the bark thickness of birch logs, but no or only minor effects on wood density. Based on our results, there is no reason to recommend the use of nonnative Baltic seed origins in Finland instead of the native locally adapted seed sources.
Keywords: bark thickness; frost crack; seed transfer; wood basic density; wood discolouration; Betula pendula; provenance; density